(3eYGdLI cGedI deTcdI GdSjhdI aj GdHfhc GdGSdGejIs - (3MOI(B, (3QGjSs ((3GdbGgQI(B:s (3ecJHI GJQGc(B,s, 2009)
(3GdfTGW GdeUQaj ddHfhc hehGQO EYGOI JLOjO GdSjhdI(B- (3eTcdI GdSjhdI hGdfTGW GdeUQaj ddHfhc GdJLGQjI (B- (3GdHfc GdeQcRj hehGQO EYGOI JLOjO GdSjhdI aj Xd fXGe eUQaj eYGUQ(B- (3GdEWGQ GdfXQj ddHfhc GdESdGejI hGdMdhd GdebJQMI deTcdI GdSjhdI aj Xd GdSjGSI GdfbOjI GddGQHhjI(B- (3EWGQ ebJQM dJWhjQ OhQ GdHfc GdeQcRj aj EYGOI JLOjO GdSjhdI aj GdHfhc GdESdGejI(B-(3YQV hJbjje dJLGQH HYV HYV GdOhd aj JWhjQ OhQ GdHfc GdeQcRj aj EYGOI JLOjO SjhdI GdHfhc GdESdGejI(B- (3GdEWGQ GdebJQM dJWhjQ OhQ GdHfc GdeQcRj aj EYGOI JLOjO GdSjhdI ddeUGQa GdESdGejI(B-(3hQ GdShb GdeGdjI GdESdGejI aj EYGOI JLOjO SjhdI GdHfhc GdESdGejIs
(3GdeQGLY U(B.509s
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfc GdeQcRjs; (3GdHfhc GdESdGejIs